Fate and behavior of dissolved organic matter in a submerged anoxic-aerobic membrane bioreactor (MBR) - Zhang, Dongqing (2020)
In this study, the production, composition, and characteristics of dissolved organic matter (DOM) in an anoxic-aerobic submerged membrane bioreactor (MBR) were investigated. The average concentrations of proteins and carbohydrates in the MBR aerobic stage were 3.96 ± 0.28 and 8.36 ± 0.89 mg/L, respectively. After membrane filtration, these values decreased to 2.9 ± 0.2 and 2.8 ± 0.2 mg/L, respectively. High performance size exclusion chromatograph (HP-SEC) analysis indicated a bimodal molecular weight (MW) distribution of DOMs, and that the intensities of all the peaks were reduced in the MBR effluent compared to the influent. Three-dimensional fluorescence excitation emission matrix (FEEM) indicated that fulvic and humic acid-like substances were the predominant DOMs in biological treatment processes. Precise identification and characterization of low-MW DOMs was carried out using gas chromatography-mass spectrometry (GC-MS). The GC-MS analysis indicated that the highest peak numbers (170) were found in the anoxic stage, and 54 (32%) compounds were identified with a similarity greater than 80%. Alkanes (28), esters (11), and aromatics (7) were the main compounds detected. DOMs exhibited both biodegradable and recalcitrant characteristics. There were noticeable differences in the low-MW DOMs present down the treatment process train in terms of numbers, concentrations, molecular weight, biodegradability, and recalcitrance.